Commentaries on 'Procalcitonin to initiate or discontinue antibiotics in acute respiratory tract infections' with a response from the review authors. Issue 4 (12th July 2013) - Sabhaney, Vikram; Enarson, Paul; Irwin, Adam D.; Carrol, Enitan D.; Schuetz, Philipp; Briel, Matthias; Bucher, Heiner C.; Mueller, Beat; ,
Abstract These are commentaries on a Cochrane review, published in this issue of EBCH, first published as: Schuetz P, Müller B, Christ‐Crain M, Stolz D, Tamm M, Bouadma L, Luyt CE, Wolff M, Chastre J, Tubach F, Kristoffersen KB, Burkhardt O, Welte T, Schroeder S, Nobre V, Wei L, Bhatnagar N, Bucher HC, Briel M. Procalcitonin to initiate or discontinue antibiotics in acute respiratory tract infections. Cochrane Database of Systematic Reviews 2012, Issue 9. Art. No.: CD007498. DOI: 10.1002/14651858.CD007498.pub2.